Quanto de Inusitado Guarda uma Sala de Aula de Matemática? Aprendizagens e erro - Clareto, Sônia Maria [UNESP]; Da Silva, Aline Aparecida (FapUNIFESP (SciELO), 2016)
A mathematics class in a public school: a usual school, a usual classroom. Everything flows as normal. However, an accurate attention to a small and trivial situation may constitute a watchful eye to simplicities in this mathematics class. As the homework was corrected, a student has doubts, the teacher explains... How consequent is this episode? In this quiet mathematics class a mistake is opened as production. A plot like a mathematics class, with the minimum of its potency. A deviation is taken as learning along with mathematics. An escape to reproduction of a model that stands, as a way that leads, to the correct result. The invention of an operation method that disquiet a thought, idealizing a thinking that breaks with the previous abordation. This article appears next to a master's dissertation in Education. In the research that generates the dissertation, there is a place beside the mathematics class in opening up to happening that there will giving.
How unusual a Mathematics class can be? Learning processes and mistakes
Keywords: Learning; Mathematics Classroom; Mistakes